Keterkaitan career goal discrepancy dan career calling dengan career decision making self efficacy pada mahasiswa - Nuru Tri Rohimah; Dian Kinayung; Widyowati, Arini (Universitas Brawijaya, 2025)
The following study aims to examine “the relationship between career goal discrepancy and career calling with career decision making self-efficacy in students”. This study involved 236 students using the cluster random sampling technique. The following study applies a quantitative approach through a scale that has met reliability standards as a data collection tool. The scales used were the “career goal discrepancy scale”, “career calling scale”, and “career decision making self-efficacy scale”. The data was analysed using multiple regression analysis techniques with the help of SPSS software. The study found that there is a very significant relationship between career goal discrepancy and career calling with career decision making self-efficacy in students at Ahmad Dahlan University. The results showed that career goal discrepancy had a significant negative relationship with career decision making self-efficacy, while career calling had a very significant positive relationship with career decision making self-efficacy.